Student teachers' team teaching: how do learners in the classroom experience team-taught lessons by student teachers?. Issue 1 (1st January 2016) - Baeten, Marlies; Simons, Mathea
Abstract: This study focuses on student teachers' team teaching. Two team teaching models (sequential and parallel teaching) were applied by 14 student teachers in a quasi-experimental design. When implementing new teaching models, it is important to take into account the perspectives of all actors involved. Although learners are key actors in the teaching process, their perspective is often ignored. Therefore, the central research question is: How do learners experience sequential and parallel teaching? A questionnaire was administered to the 229 learners participating in the experiment. Exploratory factor analysis and multilevel analysis revealed that both models were evaluated positively. However, parallel teaching scored significantly higher on advantages whereas sequential teaching scored higher on disadvantages. Quantitative content analysis revealed additional information. Benefits of parallel teaching were high levels of concentration and involvement and a positive atmosphere. In sequential teaching, learners appreciated the additional support and variation. Disadvantages of sequential teaching referred to the fact that it was confusing and to differences between both teachers. Learners in parallel teaching disliked the splitting of the class group. They were concerned that both learner groups would not be treated equally. These findings reveal that from the learners' perspective, parallel teaching should be preferred above sequential teaching.